Post genomic decade – the epigenome and exposome challenges (Swiss Medical Weekly, 2011)
Sequencing the human genome was the big challenge of the last decade. Ten years later, the large amount of DNA sequences accumulated in our databases allows us to look at genome variations between humans. The level of complexity of these variations is much higher than previously expected. It goes from changes in the nucleotidic sequence, such as single nucleotide polymorphisms (SNPs) or copy number variations (CNVs), to modifications in DNA transcription or methylation. Indeed, epigenetics, with chromatin modifications and underlying crosstalk between DNA methylation, histone tails acetylation and non coding RNAs, as microRNAs, all participate to this non-encoded gene expression regulation. Understanding the extent of genomic diversity between humans and linking it to phenotypes and diseases, unravelling the environmental exposures that may be detrimental for our health is the next challenge of the geneticists. The decrypting of the epigenome and the exposome is now on its way.